The topic of the San Lucas insular prison and in its references in the literature - Villalobos, Carlos Manuel (2021)
The San Lucas prison, located on the island of the same name, was founded in 1873. Since then, it has been the subject of interest by various Costa Rican and even foreign writers. The first story that alludes to the island is entitled Un drama en el presidio de San Lucas, published by Manuel Argüello Mora in 1900. However, the greatest literary referent corresponds to the novel La isla de los hombres solos (1963) by José León Sánchez. It also appears in other stories by this author and in narrative texts by national writers such as Carlos Salazar and Adolfo Herrera. Thanks to the novel by León Sánchez, this locus horridus has been taken to the cinema and the theater, and has motivated literary productions outside of Costa Rica. In this paper we propose a revision of these references and an analysis of discursive procedures.